The Students’ Perceptions of the Hybrid Project-Based Learning Model in the Women’s Clothing Production Course - Jamilah Jamilah; Sri Endah Wahyuningsih (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
The purpose of this study is to find out the perceptions of students from the Fashion Design Study Program in a class of 2020, Universitas Negeri Semarang, regarding applying the learning model of hybrid project-based learning in the Women's Clothing Production course. This study used a descriptive quantitative method of percentages in which the results of the research were processed and the percentages were calculated to be described descriptively. The population of this study is the students of the Fashion Design Study Program, Universitas Negeri Semarang, class of 2020, with a total of 74 students. The variable studied is the students' perception. The primary data collection method used a questionnaire supported by interviews and documentation. The results show that students' perceptions of applying a hybrid project-based learning model in the Women's Clothing Production course are seen from each perception indicator with a favorable rating with an average of 76.50% in the good category.